The Development of Interactive Learning Media Based Android Application Using Adobe Flash in Conventional Filing System - Mardiana, Adha Dwi; Hadromi, Hadromi (Journal of Vocational and Career Education, 2020)
This study aims to develop interactive learning media on Android application-based conventional filling systems, find out the level of feasibility and effectiveness of the media as well as knowing the students' responses. This research used development research methods with ADDIE development models and final test results using one group pretest-posttest design. The instruments used are questionnaires and tests. The results of media validation obtained 190 scores from media experts and a score of 339 from material experts. The assessment of media experts and materials experts declared very decent criteria. The research result of students proved to be effective since the average pretest score of 55.2 and the average posttest score of 82.3, the average difference of 27.1 with the completion of the test results achieved 86.7% from 3.3%. The t-test showed the value of tcount = 27.85 > ttable of 2.045. It means there is a significant difference, the results of the gain test get a score of 0.62 with medium improvement criteria. The final product received a very good response from students as users with a percentage of 85.4%.